2006
DOI: 10.1177/154405910608500905
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization of Enamel Caries Can Decrease Optical Reflectivity

Abstract: The remineralization of enamel caries can lead to distinct optical changes within a lesion. We hypothesized that the restoration of mineral volume would result in a measurable decrease in the depth-resolved reflectivity of polarized light from the lesion. To test this hypothesis, we measured optical changes in artificial caries undergoing remineralization as a function of depth, using Polarization-sensitive Optical Coherence Tomography (PS-OCT). Lesions were imaged non-destructively before and after exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 24 publications
4
130
0
5
Order By: Relevance
“…Based on this finding, it has been suggested that the reflectivity from the lesion area can be directly determined and then used as a measure of the lesion severity 19,20) . It has also been shown that shallow lesions exhibit a loss of penetration depth in OCT images and this is correlated with the mineral loss that can be detected with microradiography 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Based on this finding, it has been suggested that the reflectivity from the lesion area can be directly determined and then used as a measure of the lesion severity 19,20) . It has also been shown that shallow lesions exhibit a loss of penetration depth in OCT images and this is correlated with the mineral loss that can be detected with microradiography 21) .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of sound dentin, the perpendicular axis signal was relatively weaker because of light scattering and depolarization, whereas in demineralized dentin, the perpendicular axis signal was strong. Therefore, a strongly increased signal in the A-scan serves to represent the severity of demineralization 27) . In the PRG group, a higher peak signal intensity and broader width at 1/e 2 were observed, because of the occlusion of dentinal tubules by the varnish material.…”
Section: Discussionmentioning
confidence: 99%
“…In order to observe effect of demineralization to the silver staining, ground sections of artificial demineralized teeth were prepared by reference to the formation of artificial caries-like lesions 30) . Teeth were covered with dental sticky wax except for a window approximately 2 x 5 mm.…”
Section: Silver Staining Of Ground Sections Of Artificial Demineralizmentioning
confidence: 99%